Highly resolving two-dimensional gels for protein sequencing. - Hanash, S M (1991)
Two-dimensional (2D) PAGE, using carrier ampholytes for the first-dimension separation, has provided a tool for the simultaneous analysis of cellular proteins. To extend the utility of 2D PAGE to the preparative level, we have investigated the use of immobilized pH gradients (IPG) for the first-dimension separation. The results we have obtained indicate that as much as 1 mg of cellular protein can be loaded onto a single IPG gel without loss of resolution. Mutant polypeptides previously detected in carrier ampholyte-based 2D gels were equally detectable in IPG-based 2D gels. With IPG gels several hundred cellular polypeptides can be isolated, from as few as 10 gels, in sufficient amount for sequencing with current sequencing technology. We therefore conclude that IPG greatly enhances the prospects for the large-scale sequencing of cellular proteins for the development of 2D gel-related protein data bases and for the identification of new polypeptide gene products, with the attendant implications for a genome sequencing effort.